Reprogrammed CRISPR-Cas13a targeting the HPV16/18 E6 gene inhibits proliferation and induces apoptosis in E6-transformed keratinocytes - Li, Chunjing (Exp Ther Med, 2020)
The long-lasting infection of high-risk type (type 16 or type 18) human papillomavirus (HPV) is the main cause of gynecological and urinary malignancies. Given the high mortality rate after surgery, the development of a new molecular therapy would be of value to clinicians. The aim of the present study was to achieve targeted inactivation of the viral E6 gene in keratinocytes using the reprogrammed CRISPR-Cas13a system. To accomplish this, a reprogrammed CRISPR-Cas13a system, targeting both the HPV16/18 E6 genes was constructed using a guide RNA expressing vector. The expression levels of E6 protein were measured using western blot analysis after transfection of the vector into E6-transformed keratin oocytes. Cell proliferation was analyzed using CCK-8 assays and cell apoptosis was evaluated using Hoechst 33258 staining and ELISAs examining caspase-3 levels. The results indicated that both the HPV16/18 E6 genes can be inactivated using the CRISPR-Cas13a system. Furthermore, silencing E6 inhibited cell proliferation (14±1.8% on average) and induced apoptosis (80.2±3.2% on average) in E6-transformed keratinocytes but not in normal keratinocytes. In conclusion, results of the present study demonstrate that the reprogrammed CRISPR-Cas13a system has the potential for inactivating HPV E6 gene functions.